Genetic Diversity and Relationships of Phalaenopsis Based on the rbcL and trnL-F Markers: In Silico Approach - Dindin Hidayatul Mursyidin; Gusti Muhammad Zainal Ahyar; Ahmad Winarto Saputra; Aminoor Hidayat (Biosaintifika: Journal of Biology & Biology Education, 2021)
In silico is the more comprehensive and applicable approach in supporting, both conservation and breeding programs of germplasm. The study aimed to analyze and determine the genetic diversity and relationships of 24 species of Phalaenopsis using two DNA barcoding markers, namely the rbcL and trnL-F, by in silico approach. All sequences of these markers were collected randomly from the NCBI website and analyzed using several softwares and methods, such as ClustalW and MultAlin for multiple sequence alignments and MEGA-X to determine its genetic diversity and relationships. Specifically, the genetic diversity was determined using a nucleotide diversity index and their relationships by the Maximum Likelihood method. The results showed that Phalaenopsis has a low genetic diversity of 0.24, 0.32, and 0.19, respectively. The phylogenetic analysis revealed that this orchid separated into five (for the rbcL), six (trnL-F), and seven clades (a combined one), where the closest relationship is shown by P. amboinensis vs. P. venosa, whereas the farthest by P. gibbosa vs. P. doweryensis, P. stuartiana vs. P. micholitzii, and P. celebensis vs. P. pulchra. The results have novel information on the diversity and relationships of Phalaenopsis on the in silico approach. Thus, our findings might be used in supporting the conservation and breeding program of Phalaenopsis, both locally and globally.